Mental Health Conditions Among North Korean Female Refugee Victims of Sexual Violence. (9th November 2016) - Kim, Jae Yop; Kim, Hee Jin; Choi, Kwonho; Nam, Boyoung
Abstract: The study aims to examine the negative effects of sexual violence on North Korean (NK) female refugees in South Korea. Although the prevalence of sexual violence victimization is extremely high and mental health problems are serious among these refugees, little to no research has been done on the relationship between sexual violence and mental health among these women. The mental health conditions of two groups of women (sexual violence victims and those who have not experienced sexual violence) were compared using ANCOVA analyses. The results show that suicidal ideation and alcohol use are significantly more prevalent in the sexual violence group than in the non‐sexual violence group. The women who had experienced sexual violence in particular should be provided with more professional and sustained treatment and management services. The government must improve the effectiveness of existing policies related to suicide and the drinking culture in South Korea.